Investigating the Influence of Emotional Biases on the Process of Investment Decision Making: A Study of Delhi-NCR (IITM Journal of Business Studies, 2024)
The purpose of the present study is to investigate  the role of different emotional biases on the  investment decision making of the individuals.  The emotional biases studied include regret  aversion bias, herd bias, overconfidence bias,  locus of control and disposition effect bias.  The research design adopted for the study is  descriptive and exploratory in nature. The target  population of the study are the individuals  who had made any sort of investment from all  age groups, gender and profession The sample  for the study was chosen through convenience  sampling and data was collected using structured  and adapted questionnaire from both online  and offline modes. The collected data was being  analysed using structural equation modelling  with the help of SPSS and Amos software. The  results showed a significant effect of emotional  biases on the investment decision making  process of the individuals. The results of the  study can be used by the investment experts,  agents and professionals in understanding the  emotional biases of their clients impacting their  investment decisions. Thus, they can provide  requisite guidance to the investors for making  a rational decision. The major limitation of  the study includes that the sample collected  for the study is from the region of Delhi only.  Also, a limited number of emotional biases are  considered for the study. Future studies can be  performed with other emotional biases.
Keywords: Emotional, Bias; Regret; Investment Decision Making; Investors